Analysis of the Paje' Pangempang Tradition in the Perspective of the Ijarah Contract - Siti Rahma; Ahmad Abdul Mutalib; Shadriyah Shadriyah (Trescode Green Organization, 2026)
Indonesia is rich in local traditions that not only reflect cultural identity but also shape patterns of economic interaction within society. One such practice is the paje’ pangempang tradition in Tunreng Tellue Village, Bone Regency, which represents a form of cooperation between landowners and managers in utilizing pond land over a certain period. This practice is particularly interesting to examine as it inherently involves the utilization of benefits in exchange for compensation, which in Islamic law is recognized as an ijārah contract. However, the community does not explicitly identify this practice as ijārah, making it necessary to further analyze its conformity with Islamic legal principles. This study aims to examine the implementation mechanism of the paje’ pangempang tradition and analyze its conformity with the ijārah contract from the perspective of Islamic law. The research employs a qualitative method with a normative-empirical approach through interviews, observation, and documentation. The findings indicate that the practice is carried out based on clear agreements between the parties, predetermined compensation, and well-defined rights and responsibilities. Therefore, the paje’ pangempang tradition fulfills the essential pillars and conditions of the ijārah contract and can be considered consistent with Islamic legal principles.